Niepokorne: Inés Suárez i Beatriz de la Cueva, czyli kobiety u władzy w czasie podboju Ameryki Środkowej i Południowej przez Hiszpanów w XVI w. - Grzegorzewska, Kinga (Acta Universitatis Lodziensis. Folia Historica, 2015)
This article provides comparative biographies of two women: Inés Suárez and Beatriz de la Cueva. The first of whom was the mistress of Pedro de Valdivia and she took part in the conquest of Peru. The other one, was the wife of Pedro de Alvarado. She became the governor of Guatemala in place of her husband. Both women played a very important role in their Spanish communities, Inés Suárez ran the defense of Santiago de Chile, and Beatriz de la Cueva forced the city council to recognize her as the governor even after the death of her husband. Inés Suárez earned her place thanks to the power she had over Pedro de Valdivia, who was one of the most important people in the Spanish community in Chile. Beatriz de la Cueva, however, received a legit, high-power job in the public office. Both women acted contrary to generally accepted, submissive, social convention of the position of a woman and therefore both can be characterized as the unruly.